2015
DOI: 10.3390/md13106384
|View full text |Cite
|
Sign up to set email alerts
|

Tetrodotoxin, an Extremely Potent Marine Neurotoxin: Distribution, Toxicity, Origin and Therapeutical Uses

Abstract: Tetrodotoxin (TTX) is a potent neurotoxin responsible for many human intoxications and fatalities each year. The origin of TTX is unknown, but in the pufferfish, it seems to be produced by endosymbiotic bacteria that often seem to be passed down the food chain. The ingestion of contaminated pufferfish, considered the most delicious fish in Japan, is the usual route of toxicity. This neurotoxin, reported as a threat to human health in Asian countries, has spread to the Pacific and Mediterranean, due to the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
145
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(161 citation statements)
references
References 117 publications
1
145
0
2
Order By: Relevance
“…In fatal cases, humans show neurological signs within 2–3 h after exposure followed by death within 7–8 h due to respiratory failure and cardiovascular collapse [17]. Even though most intoxicated people should fully recover usually within 24 h [13], it was also reported that death may occur in less than 30 min [18], indicating a rapid rate of absorption from the gastrointestinal tract. Although hundreds of TTX intoxication cases have been published [19] it is difficult to find a correlation between toxin concentration and poisoning symptoms due to the scarce oral toxicity data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fatal cases, humans show neurological signs within 2–3 h after exposure followed by death within 7–8 h due to respiratory failure and cardiovascular collapse [17]. Even though most intoxicated people should fully recover usually within 24 h [13], it was also reported that death may occur in less than 30 min [18], indicating a rapid rate of absorption from the gastrointestinal tract. Although hundreds of TTX intoxication cases have been published [19] it is difficult to find a correlation between toxin concentration and poisoning symptoms due to the scarce oral toxicity data.…”
Section: Discussionmentioning
confidence: 99%
“…TTX is unequivocally toxic to mammals. In mice, the reported LD 50 values were 2–10, 10–10.7, 12.5–16 µg/kg BW for intravenous, intraperitoneal i.p., and subcutaneous administration, respectively [13,14]. However, at present there are no oral toxicity data of purified TTX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the origin of TTX is still unclear, although the presence of this toxin in such a diverse group of animals suggests that bacteria might be as the primary source13. In this sense, TTX can be produced without bacteria, but the presence of microorganisms could, in some way, simplify TTX biosynthesis11.…”
mentioning
confidence: 99%
“…The poisonous pufferfishes can accumulate tetrodotoxin, which is the principal neurotoxin found in pufferfish [7,22]. For a long time, tetrodotoxin was considered a metabolic product of fishes [23], but studies have demonstrated that certain bacteria, such as Vibrio sp., produce the toxin and are incorporated into fishes through the food chain [23,24].…”
Section: Poisonous Fishesmentioning
confidence: 99%